PENERAPAN MODEL COOPERATIVE LEARNING TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SD - Ameliana, Nia; Rosidah, Ani (Papanda Publisher, 2023)
The purpose of this research was to identify, describe and analyze the results of segera studies related to dd application of the Snowball Throwing type of cooperative learning model to improve social sciences elementary school learning outcomes. The Systematic Literature Review (SLR) method was used in this study, by searching the DOAJ, Scholar and Garuda databases from 2012 to 2022. Data was collected by selecting several studies based on several inclusion criteria and a total of 20 qualified articles were obtained. This study Classifies qualified primary studies based on categories such as Educational level, research method and the effectiveness of applying the Snowball Throwing type cooperative learning model to improve social studies learning outcomes. The result is that as whole, the application of the Snowball Throwing type of cooperative learning model cantik improve social studies learning outcomes and have a positive impact on learning carried out, especially studies at the elementary level. In addition, the method often used by researchers is the quantitative method which can see how the effectiveness of learning with the use of the Snowball Throwing type cooperative learning model has on student social studies learning outcomes, with the research design that is widely used namely Classroom action research.